HISTORIA NATURAL DEL TOMINEJO, COLIBRI CORUSCANS CORUSCANS (Gomn) (AVES, TROCHILIDAE) - Zerda Ordoñez, Enrique; Profesor Ornitología, Departamento de Biología, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá (2013)
olibrí coruscans is distributed on both slopes of the Central and Eastem Andes of Colombia. However, there are no reports of this species in the Westem range of the Andes. This work was carried out in «Jardín Botánico de Bogotá» for nine months during which period, territorial, breeding and feeding behavior wasstudied, through 1125 hours of observa tion. In addition,the nestling behavior during each one of the growing stages is described. Three different territorial spaces were established for Sparkling Violetear: one for display, one for nestling and another one for feeding. The former is the srnallest one and consists of only a tree branch; the nesting territory is 383m2 in size and that of feeding is 284 m2• Reproduction begins with male sexual display which consists of acrobatic flights done on one or between two trees; nest building last approximately seven days and incubation 16, with a constancy of 69%. Growing of nestlings take 21 days. The diet ofSparkling Violetear consists of nectar and insects; the former is obtained from 12 species of plants belonging to 9 families; the latter, wich was deterrilined by means of faecal bags analysis, was found to be made of insects belonging to 4 orders of which up to 60% were Díptera.